2009
DOI: 10.1111/j.1467-9477.2008.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Public Broadcasting Make a Difference? Political Knowledge and Electoral Campaigns on Television

Abstract: The political role of the modern media and the impact on public opinion has come under intense scrutiny. The arguments in the scientific dispute have been structured under the optimistic 'cognitive mobilisation' and pessimistic 'media malaise' banners. For obvious reasons the role of television has been most intensely discussed. TV has the widest reach and is believed to have to the strongest impact. So far, much of the exchange of arguments has been based on data from the United States. In many European count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 37 publications
0
15
1
2
Order By: Relevance
“…The Norwegian public broadcasting company, NRK TV, is the most popular source of political information and the most popular generally (cf. Jenssen 2009, Karlsen 2009). The average political knowledge score among the NRK-TV audience is roughly equal to those preferring national newspapers as their primary source of political information.…”
Section: The Knowledge Gap In a "Democratic Corporative" Media Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The Norwegian public broadcasting company, NRK TV, is the most popular source of political information and the most popular generally (cf. Jenssen 2009, Karlsen 2009). The average political knowledge score among the NRK-TV audience is roughly equal to those preferring national newspapers as their primary source of political information.…”
Section: The Knowledge Gap In a "Democratic Corporative" Media Systemmentioning
confidence: 99%
“…The most striking result is that public television seems to attract a more politically knowledgeable audience than the commercial TV2, and that public radio -by an even wider margin -attracts a more sophisticated audience than does the commercial P4-radio. This does not mean that public broadcasting is better at educating its audience, but rather that public broadcasting is the choice of many politically knowledgeable individuals (Jenssen 2009). Previous studies suggest that media systems with strong PB traditions are more informative with regard to "hard news" than are media systems dominated by commercial broadcasting (Aalberg et al 2008, Curran et al forthcoming).…”
Section: The Knowledge Gap In a "Democratic Corporative" Media Systemmentioning
confidence: 99%
“…According to the media malaise argument, the modern media-especially TVtend to create political cynicism and apathy, withdrawal from the sphere of public life, social isolation and consequently loss of social capital. Both the content and format of the modern media are seen as causes of the misery (Jenssen 2009). This has to be analyzed with particular caution, given that the degree of cynicism exhibited by politicians in their TV appearances has a negative effect on political trust (Mutz and Reeves 2005).…”
Section: Political (De)/mobilization Theoriesmentioning
confidence: 99%
“…Therefore, while some citizens appear to exhibit a ''spiral of cynicism'', other seem to reveal a ''virtuous circle''. Years later, Jenssen (2009) suggested that neither exposure to public nor private channels contributes to increasing the overall level of political knowledge.…”
Section: Political (De)/mobilization Theoriesmentioning
confidence: 99%
See 1 more Smart Citation